Pemodelan Sistem Penunjang Keputusan Pemilihan Calon Manajer di Suatu Perusahaan Menggunakan Metode SAW, WP dan TOPSIS - Surya Adji Pangestu; Agus Baskoro Hidayat; Ruslan Abu Honi; Sinta Nuriyah; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
A Decision Support System is a series of processes and mechanism for obtaining and processing data to be tested and used as a guide that can be used to identify problems as a basis for explaining the decision making process. SPK serves to assist the decision making process to solve problems that are semi structured or unstructured. There are three metods in the Decision Support System, among others Simple Additive Weighting method, Weighting Product method, Technique For Order Preference by Similarity to Ideal Solution method which the author will discuss in the following journal.